Look‐up table method for optimising coupling ratio in broadband sequential power amplifiers. Issue 13 (22nd September 2020) - Chen, Peng; Quaglia, Roberto; Lees, Jonathan; Merrick, Brian M.; Alt, Alexander; Tasker, Paul J.
Abstract : This study reappraises the optimum design parameters for the sequential power amplifier (SPA) when taking relative phase difference into account. By including the phase relationship between the main and peaking amplifiers, a modified efficiency formulation is derived that reveals the impacts of the key design parameters on the SPA efficiency at output power back‐off. To optimise a wideband high‐efficiency SPA design, a look‐up table method is used to predict the required coupling ratio for a wideband directional coupler. To validate the design approach, a 1.5–2.4GHz SPA is designed and measured, showing drain efficiency higher than 40% at 6dB back‐off across the band. When characterised using a 20MHz long term evolution (LTE) signal and digital predistortion, the SPA shows good linearity with error vector magnitude <1.3%, and adjacent channel leakage ratio levels better than −45 dBc across the band.